Diethylcarbamazine increases activation of voltage-activated potassium (SLO-1) currents in Ascaris suum and potentiates effects of emodepside. - Samuel K Buxton; Alan P Robertson; Richard J Martin (PLoS Neglected Tropical Diseases, 2014)
Diethylcarbamazine is a drug that is used for the treatment of filariasis in humans and animals; it also has effects on intestinal nematodes, but its mechanism of action remains unclear. Emodepside is a resistance-busting anthelmintic approved for treating intestinal parasitic nematodes in animals. The novel mode of action and resistance-breaking properties of emodepside has led to its use against intestinal nematodes of animals, and as a candidate drug for treating filarial parasites. We have previously demonstrated effects of emodepside on SLO-1 K+-like currents in Ascaris suum. Here, we demonstrate that diethylcarbamazine, which has been proposed to work through host mediated effects, has direct effects on a nematode parasite, Ascaris suum. It increases activation of SLO-1 K+ currents and potentiates effects of emodepside. Our results suggest consideration of the combination of emodepside and diethylcarbamazine for therapy, which is predicted to be synergistic. The mode of action of diethylcarbamazine may involve effects on parasite signaling pathways (including nitric oxide) as well as effects mediated by host inflammatory mediators.